2023
DOI: 10.3390/polym15081950
|View full text |Cite
|
Sign up to set email alerts
|

Review of Synthesis and Separation Application of Metal-Organic Framework-Based Mixed-Matrix Membranes

Abstract: Metal-organic frameworks (MOFs) are porous crystalline materials assembled from organic ligands and metallic secondary building blocks. Their special structural composition gives them the advantages of high porosity, high specific surface area, adjustable pore size, and good stability. MOF membranes and MOF-based mixed-matrix membranes prepared from MOF crystals have ultra-high porosity, uniform pore size, excellent adsorption properties, high selectivity, and high throughput, which contribute to their being w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…It can be correlated that the nature of particle presence on the membrane surface may be associated with the properties of ligands. 33 Accordingly, the 2-aminoterephthalic acid (ATP) ligands are likely assisting the particles to be locally distributed on the membrane surface, while the 2-methylimidazole (2M) ligands facilitate a larger distribution of particles on the membrane surface, which considerably modifies the membrane as well. 21,34 The cross-sectional images revealed that the intrinsic pore channels of the bare membrane are short-range and disrupted, as shown in Figure 3e.…”
Section: Resultsmentioning
confidence: 99%
“…It can be correlated that the nature of particle presence on the membrane surface may be associated with the properties of ligands. 33 Accordingly, the 2-aminoterephthalic acid (ATP) ligands are likely assisting the particles to be locally distributed on the membrane surface, while the 2-methylimidazole (2M) ligands facilitate a larger distribution of particles on the membrane surface, which considerably modifies the membrane as well. 21,34 The cross-sectional images revealed that the intrinsic pore channels of the bare membrane are short-range and disrupted, as shown in Figure 3e.…”
Section: Resultsmentioning
confidence: 99%
“…Growth parameters, such as reactant concentration, solvent composition, and reaction time, can be adjusted to control the membrane. 36,37 Depending on the specific substrates employed, in situ growth methods can be classified into two categories: direct growth methods and modified substrate methods.…”
Section: Environmental Science: Water Research and Technology Critica...mentioning
confidence: 99%
“…16 Today, it is known that characteristics such as the type of solvent, the salt source of the metal, the metal–ligand ratio, the capping agent and the addition of a base have an effect on the synthesis, and the size and morphology of the crystals obtained. 1,17,18 Therefore, from performing solvothermal syntheses that are typically carried out in DMF and high temperatures, 19 to green syntheses carried out in aqueous or methanolic media at room temperature, together with the aforementioned characteristics, allow the control of the morphology and size of the crystals. 20,21…”
Section: Synthesis Of Copper Mofs: Classic and Green Synthesismentioning
confidence: 99%